O aprendiz de feiticeiro: Walt Disney e a experiência norte-americana nodesenvolvimento da expressão cinematográfica docinema de animação - Wander Lucio Araujo Quintao (2007)
This work analyzes Walt Disney's and his collaborators contribution to the development of cinematographic expression of animation movies, from the elaboration of the historical, technical and aesthetical panorama of animated film. The time frame studied includes the beginning of the twentieth century in Europe, until the end of the 1930s in the United States of America, from the appearance of the rudimentary techniques of animation, with their creators and main supporters, the animated shortfilms made by the north american studios and enterprisers from the 1910s to the 1930s, mainly Walt Disney, from his early years until 1937. The aim of this work is to understand and to define the influence and the participation of the main names involved in the improvement of animated drawing, a main technique used by north american studios. We tried to maintain a chronological sequence, as a base for the analysis of representative films which are considered essential for the understanding of the development and of the technical and aesthetical changes in the art of animated film. Representative films produced in the first four decades of the twentieth century were examined, some of their main innovations were analyzed and the observations were confronted with the critics of enterprisers and scholars. The main focus of theresearch is the transposition of the classic language of the movies into the language of animation, mainly in cartoons. This movement started, with larger emphasis, with Disneys Silly Symphony series, which was the foundation for the elaborated technical and aesthetical revolution responsible for the experimentation and the changes that made the development of studios animation films possible. Therefore, a dedicatedanalysis to that historical period of Disney is the key for the understanding of the animation style developed by the studio, which turned into a modal of quality of the cinematographic industry of animated film. Among the final considerations, the need to provide a better education in visual and audiovisual arts stands out, aiming to educate the spectators into being more conscious and more aesthetically prepared to experience, an evidently indispensable characteristic when the improvement of skilledlabor formation is sought along with the expansion of animated movies in Brazil.